Poverty and Women’s Education as Determinants of Stunting and Health Rights in Riau Province - Nizmi, Yusnarida Eka; Yulia, Rahmi; Takwa, Tuah Kalti; Hidayati, Umunnisa; Wahyudi, Herry; Hasibuan, Ahmad I.R.S. (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2025)
The right to health can be fulfilled by eliminating the threat of stunting, which is primarily influenced by two major variables, poverty and the low level of education among women aged over 15. This paper analyzes the relationship between poverty, the duration of women’s education, and the prevalence of stunting in Riau Province. Women’s formal education has proven to play a critical role in reducing stunting rates by enhancing knowledge about nutrition and health. Poverty which entraps families becomes the main barrier to accessing education. A qualitative research method was employed, with data gathered through interviews, literature reviews, journals, and relevant media sources. The results indicate that basic literacy and numeracy skills acquired by women in school increase their awareness and capacity to prevent and manage stunting, thereby positively impacting the future of their children.